Reactions of o-aminothiophenol and o-aminophenyl disulfide with itaconic anhydride and (-)-dimenthyl itaconate: access to enantiomerically pure 1,5-benzothiazepines and benzothiazolyl-2-methylacrylic acid - Baag, Md. Merajuddin; Sahoo, Manoj Kumar; Puranik, Vedavati G.; N. P. Argade (Synthesis-Stuttgart, 2007)
{A facile chemo- and regioselective reactions of o-aminothiophenol (o-ATP) with itaconic anhydride is described. 1,5-Benzothiazepinyl-3-acetic acid is obtained in 81% yield via the exclusive Michael type addition of the thiol unit from o-ATP to the carbon-carbon double bond in itaconic anhydride followed by an intramolecular anhydride ring opening with an amine unit. The moderately stereoselective Michael type addition of the thiol unit from o-ATP to (-)-dimenthyl itaconate to obtain a mixture of diastereomers in a 7:3 ratio in 82% yield has been demonstrated. The reductive sulfur-sulfur bond cleavage in the dicarboxylic acid, 2({2-[2-(3-carboxybut-3-enoylamino)phenyidisulfanyl]phenylcarbamoyl\
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Regio- and stereoselective selenium dioxide allylic oxidation of (E)-dialkyl alkylidenesuccinates to (Z)-allylic alcohols: synthesis of natural and unnatural butenolides - Patel, Ramesh M.; Puranik, Vedavati G.; N. P. Argade (Organic & Biomolecular Chemistry, 2011)
The first SeO(2) induced (Z)-selective allylic alcohol formation of dialkyl alkylidenesuccinates has been demonstrated to accomplish one-step syntheses of several essential butenolides and fused butenolides via an unusual E- to Z- carbon-carbon double bond isomerisation followed by the lactonization pathway. The observed regio- and stereoselective SeO(2) allylic oxidation protocol has also been extended to the diastereoselective total synthesis of bioactive natural product isomintlactone, its direct conversion to mintlactone and an example of the base-catalyzed intramolecular rearrangement of gamma-lactone to delta-lactone.

Regioselective monoalkylation of dimethyl alkylidenesuccinates: simple approach to dialkyl-substituted maleic anhydrides including chaetomellic acid A - Kshirsagar, Umesh A.; N. P. Argade (Synthesis-Stuttgart, 2011)
Natural and nonnatural dialkylmaleic anhydrides were readily prepared from dimethyl alkylidenesuccinates by sodium hexamethyldisilazide-induced selective monoalkylation followed by base-catalyzed hydrolysis.
Keywords: alkylations; Esters; furans; heterocycles; maleic anhydrides

Regioselective NaBH4 and DIBAL-H reductions of 3,4-dimethoxyhomopiperonylphthalimide: concise and efficient synthesis of nuevamine and isonuevamine - Wakchaure, Prasad B.; Kunte, Sunita S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2011)
Facile synthesis of nuevamine and isonuevamine has been reported via the regioselectivc reduction of hindered and unhindered carbonyl groups of 3,4-dimethoxyhomopiperonylphthalimide, respectively using sodium borohydridc and diisobutylaluminum hydride, Mowed by an acid catalyzed intramolecular dehydrative cyclization pathways. The chemistry involved in obtaining the regioselectivity has been discussed in brief.
Keywords: 6-dimethoxyhomophthalimide; intramolecular dehydrative cyclizations; isonuevamine; N-Homopiperonyl-5; nuevamine; regioselective reductions; synthesis

Reactivity umpolung in intramolecular ring closure of 3,4-disubstituted butenolides: diastereoselective total synthesis of paeonilide - Deore, Prashant S.; N. P. Argade (Organic Letters, 2013)
Remarkable reactivity reversal stratagem in 3,4-disubstituted butenolides under acidic conditions is described. Design of a suitably substituted multifunctional butenolide followed by an acid-catalyzed chemo- and diastereoselective intramolecular ring closure via the reactivity umpolung has been demonstrated to accomplish a concise total synthesis of paeonilide. Overall, the present protocol involves one-pot reduction of an a,alpha,beta-unsaturated carbon carbon double bond and intramolecular nucleophilic insertion of oxygen function at the electron-rich gamma-position of butenolide. The involved mechanistic aspects have also been discussed.

Rearrangement of imine double bond in activated quinazolinones: synthesis of phaitanthrin E - Vaidya, Sagar D.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2017)
Wolff-Kishner reduction of tryptanthrin to indoloquinazolinone followed by lithium diisorpropylamide induced acylation of the active methylene group with methyl chloroformate directly furnishes the phaitanthrin E in very good yield. Similar acylations of indoloquinazolinone have also been performed with four different acyl chlorides. In all examples, facile rearrangement of imine double bond from quinazolinone to indole moiety to form the corresponding alpha,beta-unsaturated carbonyl system is observed.

Regioselective and stereoselective reductive aziridinium ring cleavage leading to azabicyclodecane architecture: enantioselective synthesis of (+)-subincanadine F - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Journal of Organic Chemistry, 2018)
Enantioselective synthesis of cytotoxic indole alkaloid (+)-subincanadine F was accomplished starting from the corresponding (S)-acetoxysuccinimide via aziridinium ring formation and its reductive ring expansion route. Regioselective and stereoselective reductive aziridinium carbon-nitrogen bond cleavage comprising ring expansions was a key step. The (S)-OMOM protection of the hydroxyl moiety adjacent to a benzylic carbon of an in situ formed aziridinium system was necessary for lithium borohydride-induced reductive ring expansions, and it also served as a latent source of an essential ketone carbonyl group for the generation of an alpha,beta-conjugated system.

Regioselective oxidation of indoles to 2-oxindoles - Shelar, Santosh V.; Argade, Narshinha P. (Organic & Biomolecular Chemistry, 2019)
Facile regioselective oxidation of indoles to 2-oxindoles promoted by sulfuric acid adsorbed on silica gel is reported. The demonstrated practical site-selective heterogeneous oxidation reactions conveniently take place with a broad substrate scope and functional group tolerances. The present oxidation strategy is also employed to accomplish the total synthesis of natural products donaxaridine and donaxarine. On the basis of analytical and spectral data it is evidenced that donaxarine stays in equilibrium with its hydrated ring opened form. The structural features essential for this type of oxidation and plausible mechanism are discussed in brief.